A Systematic Review of Technology-Supported Peer Assessment Research - Lanqin Zheng (Athabasca University Press, 2019)
With the advancement of information and communication technologies, technology-supported peer assessment has been increasingly adopted in education recently. This study systematically reviewed 134 technology-supported peer assessment studies published between 2006 and 2017 using a developed analysis framework based on activity theory. The results found that most peer assessment activities were implemented in social science and higher education in the past 12 years. Acting assignments such as performance, oral presentations, or speaking were the least common type of assignments assessed across the studies reviewed. In addition, most studies conducted peer assessment anonymously and assessors and assessees were randomly assigned. However, most studies implemented only one round of peer assessment and did not provide rewards for assessors. Across studies, it was more often the case that students received unstructured feedback from their peers than structured feedback. Noticeably, collaborative peer assessment did not receive enough attention in the past 12 years. Regarding the peer assessment tools, there were more studies that adopted general learning management systems for peer assessment than studies that used dedicated peer assessment tools. However, most tools used within these studies only provide basic functionalities without scaffolding. Furthermore, the results of cross analysis reveal that there are significant relationships between learning domains and anonymity as well as learning domains and assessment durations. Significant relationships also exist between assignment types and learning domains as well as assignment types and assessment durations.